Americanismos en la descripción geográfica del Partido de Piura by José Ignacio Lecuanda (1973) - Arrizabalaga, Carlos (2007)
The article explores the Peruvian differential lexicon of the 18th century in a typical relation of the Enlightenment, which offers numerous patrimonial terms and peculiar Indo-Americanisms of diverse origins. The terms related to the fauna of the northern Peruvian region are collected here, characterized by an extreme geography that presents numerous endemic species that have preserved autochthonous voices together with Quechua and Mochica and, of course, Castilian denominations, which show a sort of lexical stratigraphy of the linguistic history of the region.